FAMILIARIZING THE PINE NUT OIL BY FUSING IT INTO DIFFERENT FOOD PRODUCTS - Ms.R.Mahalakshmi, Ms. V.S.Charumathi, Dr.M.Inbavalli (Chelonian Research Foundation, 2023)
Pinus gerardiana (Family-Pinaceae) known as the “chilgoza” which is native to the northwestern Himalayas. There are about 29 species of pine and are utilized by indigenous tribal cultures in the world. In India, out of six species of pine, Pinus gerardiana is the only species which produces edible and highly nutritious nuts. The FAO reported that the utilization of pine nuts as a comestible food item was practiced from pre-historic times to date. Its oil is of very good quality, free of cholesterol and a rich source of fatty acids like Stearic acid (0.3%), Linoleic acid (51.3 %), Linolenic acid (1.5%), Oleic acid (39.7%), Arachidic acid (2.1%), Palmitic acid (7.2%).The extraction of pine nut oil was done using oil extracting machine in locally available small-scale industry and the extracted Pine nut oil is used to cook various recipes like Veg Pulao, Green gram sandal, Cutlet and Vegetable salad and were randomly evaluated using five-point hedonic scale and the Nutritive analysis was done laboratorically. The result showed that Veg pulao, cutlet, green gram sundal and vegetable salad prepared using pine nut oil is rich in Fat (23.31gms, 16.42 gms, 15.4 gms, 7.4gms) respectively and Protein (12.7 gms, 13.2 gms, 14.8 gms, 3 gms) respectively. It is concluded that fusion of pine nut oil in the different recipes were found to be rich in all essential fatty acids, proteins, several vitamins and minerals and were acceptable among the adolescence girls. It also helps to prevent many diseases from its occurrence. KEYWORDS: Pinus Gerardiana, Tribal culture, Edible nuts, FAO, Pre historic times, Fatty Acid, Pine Oil, Sensory Evaluation, Nutritive Analysis, Adolescence Girls.